An empirical study of the evolution of PHP MVC framework - Olanrewaju, Rashidah Funke; Islam, Thouhedul; Ali, Nor'ashikin (Springer International Publishing, 2015)
Commercial, social and educational importance of web technology has tremendously increased research activities in web programming/scripting. Several methods for writing PHP codes such as Object Oriented Programming (OOP), Procedural PHP coding and Model View Controller (MVC) pattern have been proposed. Model View Controller (MVC) which is one of the most powerful method for developing PHP application has many variant such Laravel, Symfony, CodeIgniter, CakePHP etc. However, selection of best MVC framework among the variants is of concern to the programmers as well as project managers, especially when managing big applications. Hence, performance evaluation criterions are required. This paper discusses the MVC based most famous PHP frameworks, evaluate their performance and it was found that Laravel outperforms other MVC framework, hence Laravel is proposed as the most suitable PHP framework for future web technology.